PENDETEKSIAN DERAU CITRA SECARA OTOMATIS MENGGUNAKAN TEKNIK JARINGAN SYARAF TIRUAN - Julsam julsam (Teknik Elektro Politeknik Negeri Padang, 2009)
This research is application of neural network technique to optimize convolution operation using mask 3x3 to omit the image blurring effect. This neural network consists of three layers. They are input layer (9 neuron inputs), output layer (1 output neuron) and hidden layer. Each layer is applied to 3, 5 and 7 neuron using back propagation technique. The result shows the using five neurons to hidden layer give the highest value of sound pixel recognizing (76.47%)